3-Trimethylsilyl-2-oxazolidinone, as a multifunctional additive to stabilize FEC-containing electrolyte for sodium metal batteries. (1st September 2022) - Liu, Yongchao; Jiang, Rui; Xiang, Hongfa; Huang, Zhimei; Yu, Yan
Highlight: TMSO additive effectively removes trace H2 O and corrosive HF from the electrolyte. TMSO increases the inorganic content in SEI/CEI layers to enhance ionic conductivity and stability. TMSO builds a stable CEI layer to improve the SMBs stability in FEC-containing electrolytes. SMBs exhibited remarkable electrochemical performance in the reformulated electrolyte. Abstract: Rechargeable sodium batteries have become an important complement to lithium secondary batteries and other energy devices due to their lithium-like operating mechanism and abundant sodium resources. Sodium metal batteries (SMBs) with high energy density can be applied in more aspects, but still faces more prominent challenges such as sodium dendrite growth and severe electrode-electrolyte interface reactions. Fluoroethylene carbonate (FEC) additive can effectively improve the stability of sodium metal anode due to the formation of a stable solid electrolyte interfacial (SEI) layer on sodium surface. However, the protective effect is not sufficient in suppressing sodium dendrite and corrosion of electrolyte as its easily ring-opening polymerization induced by Lewis acid (especially PF5 ) in carbonate electrolytes. Here, 3-Trimethylsilyl-2-oxazolidinone (TMSO) as a multifunctional additive that not only removes H2 O and HF from the electrolyte, but also inhibits the decomposition of NaPF6 and improves the stability of FEC-containing electrolytes. Besides, TMSO can form a stable cathode electrolyte interfacial (CEI) layer on Na3 V2 (PO4 )3 (NVP) cathode surface, alleviating NVP cracking and structural pulverization and thus endowing the long-term cycling stability of NVP cathode with low interfacial resistance. Notably, with the optimized electrolyte, the Na||NVP metal battery exhibits stable cycle performance with a capacity retention of 93.1% after 1400 cycles at room temperature and higher capacity retention of 96.6% for 270 cycles at 55 °C. Graphical abstract: Image, graphical abstract